7 uždavinys

6 uždavinys8 uždavinys

Išspręskite lygtį (x - 3)(x - 7) = 21.

A 3 ir 7

B 0 ir 10

C 10

D Sprendinių nėra

Sprendimas:

 (x-3)* (x-7)  = 
21
 (x-3)* (x-7) = 21 = 
=
( x* x- x* 7- 3* x+ 3* 7) = 21 = 
=
( x^2- x* 7- 3* x+ 3* 7) = 21 = 
=
( x^2- 10* x+ 3* 7) = 21 = 
=
( x^2- 10* x+21) = 21 = 
=
 x^2- 10* x+21 = 21 = 
 x^2- 10* x = 21-21 = 
= 0
 x^2- 10* x = 0 = 0
=
Paaiškinimas:
x iškeltas prieš skliaustus, skliaustuose liko .
 x* (x-10) = 0 = 0
x = 0 = 0
x-10 = 0 = 0
x = 0+10 = 
x = 10 = 

Atsakymas: B

6 uždavinys8 uždavinys